groEL gene-based molecular detection and antibiogram profile of Riemerella anatipestifer from duck in Bangladesh - Hasan, Alamgir; Bose, Palash; Aktar, Mst Tachhlima; Haque, Zobayda Farzana; Islam, Mohammad Rafiqul; Hossain, Muhammad Tofazzal; Siddique, Mahbubul Pratik (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: This study was designed to detect Riemerella anatipestifer through polymerase chain reaction (PCR) from duck farming areas of the Mymensingh and Sylhet divisions and to determine the antibiogram profile of the PCR-positive isolates using the disc diffusion method. Materials and Methods: Fifty two samples were collected, comprising clinically sick (32 ducks) and dead ducks(20). PCR confirmation was accomplished, and consistent findings were observed, employing R. anatipestifer groEL (271-bp) gene as appropriate molecular markers. For further clarification, see R. anatipestifer specific PCR assay (546-bp) and gyrB-based PCR (162-bp) were also done. The disc diffusion method was followed for the antibiotic susceptibility test of the isolates against commonly used antibiotics. Results: A total of 21 samples, 8 from clinically sick birds and 13 from dead birds, showed positive results in both conventional and molecular assays out of 52 samples. High occurrences were found in oropharyngeal swabs from sick ducks and the liver and heart from dead ducks. Antibiotic susceptibility testing revealed that the isolates were 100% resistant to penicillin G, cefradine, streptomycin, neomycin, gentamycin, meropenem, and erythromycin, but 100% sensitive to cotrimoxazole, florfenicol, and levofloxacin. Conclusion: For diverse duck-populated areas in Bangladesh, this study shows the severity of R. anatipestifer infection among ducks. J. Adv. Vet. Anim. Res., 9(4): 684–693, December 2022 http://doi.org/10.5455/javar.2022.i637